Association Between Cardiovascular Magnetic Resonance‐Derived Left Atrial Dimensions, Electroanatomical Substrate and NT‐proANP Levels in Atrial Fibrillation. Issue 19 (2nd October 2018) - Seewöster, Timm; Büttner, Petra; Nedios, Sotirios; Sommer, Philipp; Dagres, Nikolaos; Schumacher, Katja; Bollmann, Andreas; Hilbert, Sebastian; Jahnke, Cosima; Paetsch, Ingo; Hindricks, Gerhard; Kornej, Jelena
Abstract : Background: Enlargement of left atrial (LA) size indicates advanced disease stage in patients with atrial fibrillation (AF) and is associated with poor success of different AF therapies. Two dimensional echocardiographic LA measurements do not reliably reflect the true size of LA anatomy. The aim of the current study was: 1) to analyze cardiovascular magnetic resonance (CMR)‐derived LA dimensions and their association with low voltage areas (LVA); and 2) to investigate the association between these parameters and NT‐proANP (N‐terminal proatrial natriuretic peptide) levels. Methods and Results: Patients undergoing first AF catheter ablation were included. All patients underwent CMR imaging (Ingenia 1.5T Philips) before intervention. CMR data (LA volume, superior–inferior, transversal and anterior–posterior LA diameters) were measured in all patients. LVA were determined using high‐density maps and a low voltage threshold <0.5 mV. Blood plasma samples from femoral vein were collected before catheter ablation. NT‐proANP levels were studied using commercially available assays. There were 216 patients (65±11 years, 59% males, 56% persistent AF, 26% LVA) included into analyses. NT‐proANP levels in patients with LVA were significantly higher than in those without (median/interquartile range 22 [13–29] versus 15 [9–22] pg/mL, P =0.004). All CMR derived LA diameters correlated significantly with persistent AF ( r ²=0.291–0.468, all P <0.001), LVA ( r ²=0.187–0.306, all P <0.001), and NT‐proANP levels ( r ²=0.258–0.352, P <0.01). On logistic regression multivariable analysis, age (odds ratio=1.090, 95% confidence interval: 1.030–1.153, P =0.003), females (odds ratio=2.686, 95% confidence interval: 1.047–6.891, P =0.040), and LA volume (odds ratio=1.022, 95% confidence interval: 1.009–1.035, P =0.001) remained significant predictors for LVA. Conclusions: Left atrial CMR parameters are associated with persistent AF, low voltage areas and NT‐proANP levels. LA volume is the most significant predictor for LVA.